Beta-3-adrenergic Receptor rs4994 Polymorphism Is a Potential Biomarker for the Development of Nonalcoholic Fatty Liver Disease in Overweight/Obese Individuals. (19th December 2019) - Sakamoto, Yuki; Oniki, Kentaro; Kumagae, Naoki; Morita, Kazunori; Otake, Koji; Ogata, Yasuhiro; Saruwatari, Junji
Abstract : Nonalcoholic fatty liver disease (NAFLD) is one of the most prevalent chronic liver diseases. Obesity is the most common and well-established risk factor for NAFLD, but there are large interindividual differences in the relationship between weight status and the development of NAFLD. Beta-3-adrenergic receptor (ADRB3) plays a key role in the development of visceral obesity and insulin resistance; however, the effect of ADRB3 polymorphisms on the risk of NAFLD remains unclear. We investigated whether or not a common rs4994 polymorphism (T190C) in the ADRB3 gene is associated with the risk of NAFLD through an increase in the body mass index (BMI) among the general population. We performed cross-sectional and longitudinal analyses in a total of 591 Japanese health screening program participants. Among the overweight or obese subjects, but not normal-weight subjects, individuals with the C/C genotype had a higher risk of developing NAFLD in comparison to those with other genotypes in the cross-sectional analysis (odds ratio: 4.40, 95% confidence interval (CI): 1.08–17.93). Meanwhile, the receiver operating characteristic curve indicated that the association between an increase in the BMI and the presence of NAFLD in subjects with the C/C genotype (area under the curve: 0.91, 95% CI: 0.78–1.00) was more pronounced in comparison to subjects with other genotypes. These above-described findings were verified by the analyses using a replicated data set consisting of 5, 000 random samples from original data sets. Furthermore, among the 291 subjects for whom longitudinal medical information could be collected and who did not have NAFLD at baseline, the Cox proportional hazard model also confirmed that overweight or obese status and the C/C genotype were concertedly related to the increased risk of NAFLD development. These results suggest that genotyping the ADRB3 rs4994 polymorphism may provide useful information supporting the development of personalized BMI-based preventive measures against NAFLD.